HAMBATAN PENYELESAIAN SENGKETA TAPAL BATAS ANTARA KABUPATEN BENGKULU UTARA DENGAN KABUPATEN LEBONG BERDASARKAN HUKUM ADMINISTRASI NEGARA/HUKUM KETATANEGARAAN (JURNAL HUKUM SEHASEN, 2015)
On the issue of the boundary dispute between North Bengkulu Regency of Lebong, caused by an Act of Establishment of each area and the expansion area of Lebong resulting in a boundary dispute this. Objective: (1) determine the cause of the dispute as the border between North Bengkulu Regency of Lebong, (2) can explain Barriers boundary dispute between Lebong. This type of research used in this study is normative, because the material covered prioritize a review of the terms of the legislation relating to the Settlement Boundary between Lebong regency in Bengkulu Utara Based on Law Number 32 Year 2004 on Regional Government (replaced by Law Number 23 Year 2014 on Regional Government). Research results show that 1) Cause Boundary disputes between Lebong regency in Bengkulu Utara, described: first, the Regional Establishment Act and second, Extension Lebong regency. 2). Barriers to Settlement of disputes boundary between North Bengkulu regency of Bengkulu Lebong is the Governor's letter No. 140/021 / A / B.1. The letter, declare that the governor of Bengkulu support Formation of the District Padang Bano. The letter has been at odds with the numbers 2 Minutes of Agreement of the Region Emphasis Team, dated June 20, 2008. Keywords :  disputes / conflicts, procurement, obstacles